Влада в плитико - процесуальній площині розвитку : антропологічний контекст. - Шабанов, М.О.; Шабанов, М.О.; Shabanov, M. (My University, 2011)
Political Man is, above all, a man of power. Development of political processes begins with the development of government institutions as a result of the inﬂ uence of the so-called human factor. The actual content of modern political power remains hidden from most outsiders. Its characteristic at all possible levels of existence is the formalism. Implementation of the phenomenon of power in the political and procedural development of the plane assumes basic components. Pressing question for consideration – development of political processes and institutes in traditional societies. In the information society of political power in an anthropological context of development is doomed to dependence on government – owned.
Шабанов М.О.Влада в плитико - процесуальній площині розвитку : антропологічний контекст. / М.О.Шабанов // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 12-18 . С 138 - 148.
Keywords: Влада; Феномен влади; Влада в політико - процесуальній площині; Власть; Феномен власти; Власть в политико - процесуальной плоскости; Power in politics - protsesualnoy plane; The phenomenon of power; power